Perancangan Booth Flatpack untuk Bazar Makanan dan Minuman di Mall Surabaya - Pauline Christina; Grace Mulyono; Franky Tanaya (Intra, 2019)
Pop-up markets, bazaars, and other similar market are effective alternatives for enterpreneurs to expand their business. Supporting facility to make their sales effective is required. Based on survey, the challenge that must be faced in these events are limited time and area provided by the organizer. Therefore, a well-designed booth as a solution, was made through Kembel’s design method in five steps, which are Emphatize (find the problem), Define (defining the essence of the problem), Ideate (seeking creative ideas), Prototype (creating the design as solution), and Test (assessing the design result in solving the problem). The design solution is to create practical furniture in flatpack design as an efficient answer both in mobility and economic aspects.